A Study on the Association between Therapeutic Community Program and Social Relationship of Previously Addicated Persons - Seyyed Jalal Sadrosadat; Zahra Mohammadi-Rostam Kalateh; Alireza Keldi (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: The main aim of this research was to investigate the effects of therapeutic community program on social relationship of previous addicated persons. Materials & Methods: The method of treatment in therapeutic community (TC) program was used in accordance with providing conditions for mental and social development of addicted persons. A group of subjects (n=30) with an age range of 20 - 25 years were selected to test the effects of resocialization on their interactions with other people. Results: Based on the results, TC program including morning meetings, psychology course, individual and group counseling can be used to measure the improvement of social relationship of the individuals with the correlation of r=0.41 with P=0.03. Conclusion: The results show that with the increase of participation of individuals in TC programs, the improvement in social relationships of them will be achieved.